BRAND IMAGE, SALES PROMOTION, DAN SOCIAL COMMERCE SEBAGAI DETERMINAN PURCHASE INTENTION PRODUK AEROSTREET DI DENPASAR - Wahyu Pidada Pemaron, Ida Bagus; Prawitasari, Putu Putri; Anjani, Ni Ketut; Manik Parasari , Nyoman Sri (LP2M Universitas Bina Bangsa, 2025)
The aim of this research is to evaluate both the individual and combined impacts of social commerce, promotional activities, and brand perception on consumers' purchase intentions. This study included up to 120 participants from Generation Z who had purchased Aerostreet products. Validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, F-test, and t-test were used to analyze the data. The study's findings indicate that social commerce, sales promotions, and brand image all have a favorable and significant impact on purchase intentions. The impact of the independent factors on purchase intention is 52.1%. Researchers suggest that Aerostreet could work with influencers on promotions so that more customers are interested in acquiring their products. Aerostreet must continue to engage clients in continuity initiatives, offer items that fit customers' lifestyles, and consistently produce products that outperform competition.